Lag-Lead Compensator for Shape Memory Alloy in Gripping Manipulation - Made Andik Setiawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
Shape Memory Alloy (SMA) is emerging actuator for micro and nano application which is interesting to be developed. This paper presents the evaluation of close-loop controller responses of the TiNi SMA spring based gripper by introducing lag, lead and lag-lead compensator. A SMA spring has a diameter of 50 mm wire and 350 gram hanging mass. The driver of the SMA actuator uses pulse width modulation (PWM) signal and it is tested by varying frequencies and duty-cycles. The applied frequencies in this study are 12, 25, 125, 250 and 1150 Hz. Lab-View and DAQ-Card is used as a controller, interfacer and data recorder of the system. The fabricated gripper consists of two fingers and the total angular displacement of the gripper is 300. In advanced application, the experiment coversSMA open loop and close-loop system. The SMA response indicated that the rise-time and the steady-state error of the cloop-loop are shorter and lower than open-loop controller.